Age-dependent benefit of neoadjuvant treatment in adenocarcinoma of the esophagus and gastroesophageal junction: a multicenter retrospective observational study of young versus old patients - Rompen, Ingmar F.; Crnovrsanin, Nerma; Nienhüser, Henrik; Neuschütz, Kerstin; Fourie, Lana; Peters, Leila; Müller, Beat P.; Billeter, Adrian (International journal of surgery, 2023)
Objectives: - The objective was to provide evidence for age-dependent use of neoadjuvant treatment by clinical comparisons of young (lower quartile, <56.6 years) versus old (upper quartile, >71.3 years) patients with esophageal and esophagogastric-junction adenocarcinoma. - Background: - Neoadjuvant treatment is the standard of care for locally advanced and node-positive EAC. However, the effect of age on oncological outcomes is disputable as they are underrepresented in treatment defining randomized controlled trials. - Methods: - Patients with EAC undergoing esophagectomy between 2001 and 2022 were retrospectively analyzed from three centers. Patients having distant metastases or clinical UICC-stage I were excluded. Cox proportional hazards regression was used to identify the variables associated with survival benefit. - Results: - Neoadjuvant treatment was administered to 185/248 (74.2%) young and 151 out of 248 (60.9%) elderly patients (P=0.001). Young age was associated with a significant overall survival (OS) benefit (median OS: 85.6 vs. 29.9 months, hazard ratio 0.62, 95% CI: 0.42-0.92) after neoadjuvant treatment versus surgery alone. In contrast, elderly patients did only experience a survival benefit equaling the length of neoadjuvant treatment itself (median OS: neoadjuvant 32.8 vs. surgery alone 29.3 months, hazard ratio 0.89, 95% CI: 0.63-1.27). Despite the clear difference in median OS benefit, histopathological regression was similar ((Mandard-TRG-1/2: young 30.7 vs. old 36.4%, P= 0.286). More elderly patients had a dose reduction or termination of neoadjuvant treatment (12.4 vs. 40.4%, P<0.001). - Conclusion: - Old patients benefit less from neoadjuvant treatment compared to younger patients in terms of gain in OS. Since they also experience more side effects requiring dose reduction, upfront surgery should be considered as the primary treatment option in elderly patients.
Online veröffentlicht: 14. September 2023
Gesehen am 10.06.2024